2019
DOI: 10.24256/ideas.v7i1.714
|View full text |Cite
|
Sign up to set email alerts
|

Motivation Behind Indonesian Undergraduates Learning English as a Target Language

Abstract: Learning English as a target language (LETL) is likely learning something that is not native to undergraduates of Indonesian language. For this reason, if they learn the target language determination should be kept and motivation should be filled as well. This study is aimed at of knowing the influence of motivation in Indonesia department undergraduates’ performance when learning English as a target language in English classroom setting. The method chosen for this study is a quantitative approach in the form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…Interestingly, this finding appears to affirm the results of similar studies in the past conducted by Budiharto and Amalia (2019). According to them, motivation was the key incentive of learners' performance in learning a target language.…”
Section: The Motivation Of Learning a Foreign Languagesupporting
confidence: 88%
See 3 more Smart Citations
“…Interestingly, this finding appears to affirm the results of similar studies in the past conducted by Budiharto and Amalia (2019). According to them, motivation was the key incentive of learners' performance in learning a target language.…”
Section: The Motivation Of Learning a Foreign Languagesupporting
confidence: 88%
“…This finding supports Alberth's (2018) idea of ideal L2 self in Indonesian EFL context, that is "ideal L2 self may be interpreted as being a proficient speaker of English, in which the skills could enable the learners to interact with the international community or to get a better job in the globalized world". It was also consistent with the results of an investigation of undergraduate students' motivational orientations for learning English, which found that ideal L2 self was the most underlined motivational dimension of the students in learning English (Budiharto & Amalia, 2019).…”
Section: The Motivation Of Learning a Foreign Languagesupporting
confidence: 88%
See 2 more Smart Citations
“…In Indonesia, language input might come from language courses, schools, native teachers, books, novels, community, Etc. However, the majority of English as a Foreign Language (EFL) students in Indonesia rely mostly on routine classroom instruction to improve their English proficiency (Budiharto & Amalia, 2019;Pratiwi, A. W. et al, 202). Wang (2010:102-103) also stated that the majority of EFL students in China only learn foreign languages in the classroom.…”
Section: Introductionmentioning
confidence: 99%